- #1

- 190

- 0

**1. Find C and S in terms of the initial position and velocity of the oscillator.**

Give your answers in terms of x_0, v_0, and omega. Separate your answers with a comma.

Give your answers in terms of x_0, v_0, and omega. Separate your answers with a comma.

**2. x(t) = X_0 + v_0*t + 0.5at^2**

x(t) = C*cos(omega*t) + S*sin(omega*t)

x(t) = C*cos(omega*t) + S*sin(omega*t)

**3. Taking the derivative of x(t):**

v(t) = -C*omega*sin(omega*t) + S*omega*sin(omega*t)

Thus,

x_0 = C

v_0 = S*omega

How don't quite see how to solve for C and S in terms of x_0, v_0, and omega only.

v(t) = -C*omega*sin(omega*t) + S*omega*sin(omega*t)

Thus,

x_0 = C

v_0 = S*omega

How don't quite see how to solve for C and S in terms of x_0, v_0, and omega only.